Influence of Host Factors on Immunoglobulin G Concentration in Oral Fluid Specimens - Granade, Timothy C. (American Society for Microbiology, 2002)
The influence of host factors (tobacco use, dentition, bleeding gums, oral rinsing, nasal medications, and time since the last meal) on immunoglobulin G (IgG) concentration in oral fluids (OF) was determined by univariate and multivariate analysis. Significant differences in IgG concentration were found to be associated with human immunodeficiency virus (HIV) status (HIV antibody positive, +16.60 μg/ml, P = 0.0001), sex (female, +1.23 μg/ml, P = 0.004), dentition (+2.83 μg/ml, edentulous versus dentulous, P = 0.0001), bleeding gums (+6.35 μg/ml, P = 0.0001), and time since the last meal (+3.55 μg/ml, >6 h, P = 0.0001). These factors could impact diagnostic methods that rely on the immunoglobulin concentration in OF specimens.